Protective Effect of Remdesivir Against Pulmonary Fibrosis in Mice - Xiaohe Li; Xiaohe Li; Rui Liu; Rui Liu; Yunyao Cui; Yunyao Cui; Jingjing Liang; Jingjing Liang; Zhun Bi; Shimeng Li; Shimeng Li; Yang Miao; et al. (Frontiers Media S.A., 2021)
Pulmonary fibrosis is a known sequela of severe or persistent lung damage. Existing clinical, imaging and autopsy studies have shown that the lungs exhibit a pathological pulmonary fibrosis phenotype after infection with coronaviruses, including severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Pulmonary fibrosis may be one of the most serious sequelae associated with coronavirus disease 2019 (COVID-19). In this study, we aimed to examine the preventative effects of the antiviral drug remdesivir on pulmonary fibrosis. We used a mouse model of bleomycin-induced pulmonary fibrosis to evaluate the effects of remdesivir on pulmonary fibrosis in vivo and further explored the potential pharmacological mechanisms of remdesivir in lung fibroblasts and alveolar epithelial cells in vitro. The preventive remdesivir treatment was started on the day of bleomycin installation, and the results showed that remdesivir significantly alleviated bleomycin-induced collagen deposition and improved pulmonary function. In vitro experiments showed that remdesivir dose-dependently suppressed TGF-β1-induced lung fibroblast activation and improved TGF-β1-induced alveolar epithelial to mesenchymal transition. Our results indicate that remdesivir can preventatively alleviate the severity of pulmonary fibrosis and provide some reference for the prevention of pulmonary fibrosis in patients with COVID-19.